2020
DOI: 10.3390/pharmaceutics12121189
|View full text |Cite
|
Sign up to set email alerts
|

The Delivery of the Novel Drug ‘Halicin’ Using Electrospun Fibers for the Treatment of Pressure Ulcer against Pathogenic Bacteria

Abstract: Pressure ulcer or bedsore is a form of skin infection that commonly occurs with patients admitted to the hospital for an extended period of time, which might lead to severe complications in the absence of medical attention, resulting in infection either by drug-sensitive or drug-resistant bacteria. Halicin, a newly discovered drug effective against several bacterial strains, including multidrug-resistant bacteria, was investigated to reduce bacterial infection burden. This study aims to formulate halicin into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 54 publications
16
20
0
Order By: Relevance
“…The spectrum showed two broad bands at 3650–3100 and at 3030–2790 cm −1 that were related to the O–H stretching, from adsorbed water, and the C–H stretching, respectively. This spectrum is consistent with the PVP IR spectrum of [ 33 , 35 , 44 , 47 , 55 ]. The stretching peaks of PVP at 1656 cm −1 and between 3650 and 3100 cm −1 were present in the PM, blank, and drug-loaded fibers IR spectra.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The spectrum showed two broad bands at 3650–3100 and at 3030–2790 cm −1 that were related to the O–H stretching, from adsorbed water, and the C–H stretching, respectively. This spectrum is consistent with the PVP IR spectrum of [ 33 , 35 , 44 , 47 , 55 ]. The stretching peaks of PVP at 1656 cm −1 and between 3650 and 3100 cm −1 were present in the PM, blank, and drug-loaded fibers IR spectra.…”
Section: Resultssupporting
confidence: 87%
“…Consequently, a slower dissolution rate can be obtained, compared to lower MW PVP. Similar MW PVP was used by Rasekh et al and Aburayan et al for preparing indomethacin- and halicin-loaded fibers, respectively; the full drug release for both studies was reported to be over 30 min [ 55 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The yeast C. albicans —ATCC 66,027 was obtained from ATCC. The bacterial and yeast suspensions, also known as inoculums, were all prepared in Mueller–Hinton broth by measuring 0.5 McFarland, according to [ 19 ]. All microorganisms were cultured on Mueller–Hinton agar medium and incubated at 37 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…New infections, bacterial or viral, have often raised significant threats to public health across the globe. One of these hazardous pathogens is severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is renowned to cause coronavirus disease 2019 (COVID- 19) that was declared a global pandemic by the World Health Organization (WHO) at the beginning of 2020 [1]. After its discovery in Wuhan in December 2019, more than 150 million confirmed cases have occurred worldwide by April 2021.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial strains that were tested included; Acinetobacter baumannii ( A. baumannii ) BAA 747, two strains of Escherichia coli ( E. coli ) ATCC 25,922 and a clinical isolate 1060, Klebsiella pneumoniae ( K. pneumoniae ) BAA 1705, two strains of Pseudomonas aeruginosa ( P. aeruginosa ) BAA 1744 and ATCC 27853, Staphylococcus aureus ( S. aureus ) ATCC 29213, Staphylococcus epidermidis ( S. epidermidis ) clinical isolate 5029, Staphylococcus hominis ( S. hominis ) clinical isolate 5028, Staphylococcus haemolyticus ( S. haemolyticus ) clinical isolate 5034, and Micrococcus luteus ( M. luteus ) environmental isolate SB 115. Bacterial inoculums were prepared in Mueller-Hinton broth by measuring 0.5 McFarland, as previously reported ( Aburayan et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%